Štajeriš Podoba in kontekst slovenskega ljudskega plesa - Kunej, Rebeka (Folkloristika, 2012)
The book's main goal is to present one of the Slovenian folk dances, štajeriš (Steierisch or Steirisch), from choreological and dance-anthropological perspective. The introductory chapter frames the topic geographically, temporally and theoretically and provides the basis for the following two extensive chapters. The first part of the book is focused on the dance itself. It presents morphological and structural analysis of dance, leading to a morphological-structural analysis of the Slovenian štajeriš, with the primary structure derived from the number of dancers. In the second part of the book, the focus shifts from a dance to men. It starts off by presenting the syncretism of a dance, music and song in the štajeriš, to later focus on the role and meaning in man's life, with the last section discussing the relationship between the men and the dance, where the dance is treated as a medium trough which both verbal and nonverbal communications is made possible. The central chapters are rounded off by a short chapter on the state of the štajeriš today, where it actually no longer lives among the people, but appears only as the revival of the past. In appendix, the book presents three previously unpublished records (Kinetography Laban scores) of štajeriš.